Evaluating Aid for Trade : A Survey of Recent Studies - Cadot, Olivier; Fernandes, Ana; Gourdon, Julien; Mattoo, Aaditya; de Melo, Jaime (World Bank, Washington, DC, 2014)
The demand for accountability in aid-for-trade is increasing but monitoring has focused on case studies and impressionistic narratives. The paper reviews recent evidence from a wide range of studies, recognizing that a multiplicity of approaches is needed to learn what works and what does not. The review concludes that there is some support for the emphasis on reducing trade costs through investments in hard infrastructure (like ports and roads) and soft infrastructure (like customs). But failure to implement complementary reform -- especially the introduction of competition in transport services -- may erode the benefits of these investments. Direct support to exporters does seem to lead to diversification across products and destinations, but it is not yet clear that these benefits are durable. In general, it is difficult to rely on cross-country studies to direct aid-for-trade. More rigorous impact evaluation is an underutilized alternative, but situations of clinical interventions in trade are rare and adverse incentives (because of agency problems) and costs (because of the small size of project) are a hurdle in implementation.